CULTURING AIRWAY POLYMICROBIAL COMMUNITIES UNDER CONTINUOUS FLOW CONDITIONS - Puri, Akshita (My University, 2013)
Microbes are ubiquitous in the biosphere and play important roles in natural ecosystems. They are typically present as diverse, complex communities, and in humans these communities are present on all exposed surfaces and mucosal tissues. The human upper respiratory tract harbors a complex microbiome and the composition includes what are traditionally considered commensal organisms, including a significant proportion of anaerobic bacteria. It is generally assumed that most of the bacteria from any particular environment cannot be readily cultivated, including the human microbiome. Some in vitro microfluidic and in vivo models are available to study the airway microbial communities, however these methods are expensive, limited and are not practical for experiments manipulating the community. A robust culture-based approach that can propagate these polymicrobial communities has been developed in this study to investigate spatial-temporal changes in bacterial populations in vitro. Matrix embedded synthetic bacterial communities, comprised of aerobes and anaerobes, were cultivated in continuous flow cell systems. The structure of communities propagated in these systems was compared to those in static and shaken batch cultures. The data shows that reproducible stable bacterial communities can be propagated with these culture methods, however the community composition varies considerably with the approach used. Only matrix embedded communities, cultured under continuous flow conditions, could successfully retain obligate anaerobes when flow cell systems were operated in an aerobic environment. This optimized method was used for culturing complex and diverse natural communities from clinical samples (sputum). The majority of bacteria present in the original sample were recovered in flow cell cultures and the methodology was consistent. This study provides an experimental system that can be used for examining microbial community dynamics and community structure-function relationship.
Keywords: Bacteriology; Environmental Microbiology and Microbial Ecology; Bacteriology